A lattice boltzmann method for modeling the dynamic pole-to-pole oscillations of min proteins for determining the position of the midcell division plane - Waipot Ngamsaad (2018)
Determining the middle of the bacteria cell and the proper placement of the septum is essential to the division of the bacterial cell. In E. coli, this process depends on the proteins MinC, MinD, and MinE. Here, the lattice Boltzmann method (LBM) is used to study the dynamics of the oscillations of the min proteins from pole to pole. This determines the midcell division plane at the cellular level. The LBM is applied to the set of deterministic reaction diffusion equations proposed by Howard et al, to describe the dynamics of the Min proteins. The LBM results are in good agreement with those of Howard et al. and agree qualitatively with the experimental results. Our good results indicate that the LBM can be an alternative computational tool for simulating problems dealing with complex biological systems that can be described by using the reaction-diffusion equations.